(untitled) (Research, Society and Development, 2020)
Objective: Analyze the severity of drug incompatibilities in an intensive cardio unit. Methods: Observational study, with cross-sectional design and quantitative in nature. Study based on two steps: verification of the prescriptions and direct observation of the infusion in the patient, to identify the incompatibility in loco. Data collection took place from September 2018 to May 2019 using an own collection instrument, performed in the intensive cardio unit of a University Hospital in Rio de Janeiro. Results: 161 drug prescriptions were observed, with the identification of 2,227 drugs, of which 858 (38.52%) were administered intravenously. Among these, 631 (73.54%) medications were administered simultaneously. Among these drugs, 893 doses were administered simultaneously, of which they were analyzed for incompatibility and the severity of the incompatibility. 271 compatibilities were identified (30.35%); 94 incompatibilities (10.52%), and 528 untested combinations (59.13%). Conclusions: The combinations of medications identified as the most frequent serious ones were: Midazolam with Imipenem (8.51%), Midazolam with Hydrocortisone (8.51%), Fentanyl with Amiodarone (7.44%) and Polymyxin B with Furosemide (6.38 %). Critical patients are the most vulnerable to the occurrence of drug incompatibilities, highlighting the need for further studies, in order to provide greater safety for the administration of intravenous drugs.